2021
DOI: 10.1111/mec.16163
|View full text |Cite
|
Sign up to set email alerts
|

Microbes support enhanced nitrogen requirements of coral holobionts in a high CO2 environment

Abstract: Ocean acidification is posing a threat to calcifying organisms due to the increased energy requirements of calcification under high CO2 conditions. The ability of scleractinian corals to cope with future ocean conditions will thus depend on their ability to fulfil their carbon requirement. However, the primary productivity of coral holobionts is limited by low nitrogen (N) availability in coral reef waters. Here, we employed CO2 seeps of Tutum Bay (Papua New Guinea) as a natural laboratory to understand how co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 84 publications
1
21
0
Order By: Relevance
“…Sample collection took place during the boreal spring, between May 26th and June 7th 2018, aboard the R/V Alis, as described in Meunier et al (2021b). At a hydrothermal vent area at Tutum Bay (Ambitle Island, New Ireland Province, Papua New Guinea), samples were collected from one site exposed to high pCO 2 (4 • 3 44.82 S 153 • 34 56.09 E) and one reference (control) site with ambient pCO 2 (4 • 4 0.60 S 153 • 34 41.43 E) located ca.…”
Section: Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sample collection took place during the boreal spring, between May 26th and June 7th 2018, aboard the R/V Alis, as described in Meunier et al (2021b). At a hydrothermal vent area at Tutum Bay (Ambitle Island, New Ireland Province, Papua New Guinea), samples were collected from one site exposed to high pCO 2 (4 • 3 44.82 S 153 • 34 56.09 E) and one reference (control) site with ambient pCO 2 (4 • 4 0.60 S 153 • 34 41.43 E) located ca.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Samples were immersed in DNA/RNA Shield (Zymo, Freiburg, Germany) and shipped on dry ice for DNA extraction, nifH amplification, and sequencing. The P. damicornis samples are the same as those analyzed in Meunier et al (2021b).…”
Section: Sample Collectionmentioning
confidence: 99%
“…The diameter of each circle is proportional to the abundance of the group. Baghdasarian et al, 2017;Krueger et al, 2017;Meunier et al, 2021;Zhou et al, 2021). For example, Noonan and Fabricius (2015) studied the response of Seriatopora hystrix and Acropora millepora to ocean acidification, finding that elevated CO 2 partial pressure (pH 7.79) had no adverse effects on both coral (Noonan and Fabricius, 2015).…”
Section: Acropora Valida Shows Strong Adaptability To Ocean Acidificationmentioning
confidence: 99%
“…The increase in Cyanobacteria is likely to provide compensation for the photosynthesis of coral holobiont, ensuring the energy supply that is needed by corals in low pH environments. A new study by Meunier et al (2021) found that at the CO 2 seeps of Tutum Bay (PNG), P. damicornis modified its N assimilation pathways by utilizing picoplanktonsized unicellular Cyanobacteria (Synechococcus sp.) in oligotrophic waters to offset the increasing N requirements under high CO 2 (Meunier et al, 2021).…”
Section: Changes In the Composition Of The Coral-associated Bacteria Help Corals Adapt To An Acidified Environmentmentioning
confidence: 99%
See 1 more Smart Citation